Transcriptome analysis provides novel insights into the factors influencing the settlement and metamorphosis of Pinctada maxima - Minxin Liang; Wenhao Yu; Kaiyao He; Qingheng Wang; Yongshan Liao; Ronglian Huang; Dewei Cheng; Yuewen Deng; Zhe Zheng; Chuangye Yang (Aquaculture Reports)
The metamorphosis of the planktonic larvae of bivalve species plays a key role in their complex life history strategies, and this process involves changes in the molecular machinery required for sessile life and the development of intricate shells. Understanding the key molecular agents and special requirements in this development stage is critically important for increasing the production of larvae and promoting population recovery. Here, we cultured larvae of the giant pearl oyster Pinctada maxima, a protected bivalve species in China that is used for the commercial production of large pearls. RNA sequencing was used to identify differentially expressed genes (DEGs) before (E) and after metamorphosis (ES). A total of 8270 DEGs were identified. The up-regulation of genes related to oxidative phosphorylation at the ES stage indicate an increase in energy metabolism. The DEGs were systematically determined by conserved domain analysis. DEGs involved in apoptosis and autophagy coincided with changes in morphology and tissue reconstruction at the metamorphosis stage. In addition, the increased expression of genes related to hormone, neurotransmitter/neuropeptide receptor, and immunitye at the ES stage suggests that they play an important role in the induction of various metabolic processes and the development of the immune system following exposure to new environments. The high expression of vitamin B transporters indicates that the absorption and bioavailability of vitamin B are particularly important for the metamorphosis of P. maxima. These findings provide new insights into the factors inducing metamorphosis and the nutritional requirements of rare bivalve species, which have implications for the population restoration and breeding of bivalves.